Identification, assessment and reporting of suspected Adverse Drug Reactions (ADRs) to Anti-retroviral therapy (ART) and Anti-tubercular therapy (ATT) in a community care centre at Warangal (World Journal of Current Medical and Pharmaceutical Research, 2019)
Adverse effects of drugs are the main source of morbidity and mortality among the outpatients and inpatients. The objective of the study was to identify, assess and report suspected Adverse Drug Reactions in patients who are diagnosed with Human Immunodeficiency Virus-Acquired Immunodeficiency Syndrome (HIV-AIDS) patients with and without tuberculosis (TB). This was a prospective observational study conducted for a period of six months to explore the significant ADRs caused by Anti-Retroviral and Anti-Tubercular drugs in patients visiting the community care center at Warangal who are diagnosed with HIV-AIDS with or without Tuberculosis as co-infection. In our study, we enrolled 144 patients and a total of 514 ADRs were identified in 125 patients. The most common ADR observed in our study was peripheral neuropathy in 61 patients, followed by vomitings, weakness, anorexia, myalgia, diarrhea, and itching. The ART regimen Stavudine+Lamivudine+Efavirenz (STV+LMV+EFV) was found to be most commonly involved in about 138 ADRs, whereas the regimen Zidovudine+Lamivudine+Nevirapine (ZDV+LMV+NVP) was found to be having the least incidence rate of ADRs. Causality assessment was made using the WHO probability scale and Naranjo’s Scale and 340 (66.14%) and 346 (67.31%) ADRs were classified into Possible respectively. The severity of ADRs were assessed using Hartwig scale and 376 (67.50%) ADRs were classified into Moderate and 138 (26.84%) into Mild ADRs. The findings of our study showed that a huge number of ADRs were experienced by the patients who are receiving ART and ATT which is a major cause for medication Non-compliance and discontinuation of the therapy. Therefore, close monitoring and reporting of ADRs are needed in these patients who are receiving ART and ATT.